Effect of Heat Treatment Temperature on Hardness of Jaw Implant Produced from EDM Die-Sinking Process - M. F. R. Suharyanto; Yani Kurniawan (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Hardness is the main problem in making jaw implants using the die-sinking EDM process. Heat treatment can increase the hardness of jaw implants resulting from the EDM process. This research investigates the influence of temperature during the heat treatment process on the hardness of jaw implants produced from the EDM process. Heat treatment uses a quenching process. The quenching temperatures used were 940, 950, and 960 ºC, while the holding time was 30 minutes. The aging temperature is 550 ºC. The research results show that the greater the quenching temperature, the greater the increase in hardness. The hardness of the white layer reaches 713 VHN when using a temperature of 960 ºC. Meanwhile, the hardness of the inner jaw implant reaches 354 VHN.